The effect of exercise intensity on brain derived neurotrophic factor and memory in adolescents - Yong Kyun Jeon; Chang Ho Ha (Komiyama Printing Co. Ltd, 2017)
Abstract Background Brain derived neurotrophic factor (BDNF) seems to serve as an important regulatory mechanism in the growth and development of neurons in many areas of the brain.Insulin-like growth factor 1 (IGF-1) is related to neurogenesis and regulation of the BDNF gene and is involved in the growth and differentiation of neurons.Cortisol is released in response to stimuli such as psychological oppression, anxiety, and fear. Stress also induces changes in BDNF. The purpose of this study was thus to examine the effects of varying intensities of aerobic exercise on resting serum BDNF, IGF-1 concentrations, cortisol, and memory of adolescents. Methods Forty male students with no history of physical illness from the middle school by participated in this study. Participants were randomly assigned to low, moderate, or high intensity treadmill exercise group, or a stretching (control) group. Exercise was performed 4 times per week for 12 weeks. Body composition, brain derived neurotrophic factor levels, insulin-like growth factor 1 levels, cortisol levels, and working memory were assessed. Results The high intensity exercise group showed a significant increase in brain derived neurotrophic factor at rest, concentration level of insulin-like growth factor 1, cortisol, and working memory. For resting brain derived neurotrophic factor, the high intensity exercise group showed a more significant increase compared to the low intensity aerobic and stretching groups. The change in the working memory significantly increased for the high intensity exercise group compared to the low intensity aerobic group, moderate intensity exercise group, and stretching group. Conclusions In adolescents, whose brains are still developing, aerobic exercise of moderate to high intensity levels seems to have a positive effect on levels of serum brain derived neurotrophic factor at rest and on cognitive functioning. Trial registration EHPM-D-16-00107R2 . ICMJE. 12 July 2016.